Fast Magnetic Measurements Of 8.6 m Undulator - Davidyuk I.V.; Gorbachev Ya.I.; Shevchenko O.A. (EPJ Web of Conferences, 2018)
The design of the large-aperture variable-period undulator (VPU) developed for the Novosibirsk free electron laser (FEL) is shortly described. High amplitude of on-axis field is achieved due to the arc shape of the magnet blocks and poles of the undulator. To conduct magnetic measurements and fine tuning of the undulator as well as to perform real time position tracking of magnet blocks, pulsed wire technique was adopted.